COVID-19-Associated Pulmonary Embolism: Review of the Pathophysiology, Epidemiology, Prevention, Diagnosis, and Treatment - Ortega-Paz, Luis; Talasaz, Azita H.; Sadeghipour, Parham; Potpara, Tatjana S.; Aronow, Herbert D.; Jara-Palomares, Luis; Sholzberg, Michelle; Angiolillo, Dominick J.; Lip, Gregory Y.H.; Bikdeli, Behnood (Seminars in Thrombosis and Hemostasis, 2022)
COVID-19 is associated with endothelial activation in the setting of a potent inflammatory reaction and a hypercoagulable state. The end result of this thromboinflammatory state is an excess in thrombotic events, in particular venous thromboembolism. Pulmonary embolism (PE) has been of special interest in patients with COVID-19 given its association with respiratory deterioration, increased risk of intensive care unit admission, and prolonged hospital stay. The pathophysiology and clinical characteristics of COVID-19-associated PE may differ from the conventional non–COVID-19-associated PE. In addition to embolic events from deep vein thrombi, in situ pulmonary thrombosis, particularly in smaller vascular beds, may be relevant in patients with COVID-19. Appropriate prevention of thrombotic events in COVID-19 has therefore become of critical interest. Several changes in viral biology, vaccination, and treatment management during the pandemic may have resulted in changes in incidence trends. This review provides an overview of the pathophysiology, epidemiology, clinical characteristics, and risk factors of COVID-19-associated PE. Furthermore, we briefly summarize the results from randomized controlled trials of preventive antithrombotic therapies in COVID-19, focusing on their findings related to PE. We discuss the acute treatment of COVID-19-associated PE, which is substantially similar to the management of conventional non-COVID-19 PE. Ultimately, we comment on the current knowledge gaps in the evidence and the future directions in the treatment and follow-up of COVID-19-associated PE, including long-term management, and its possible association with long-COVID.
Keywords: SARS-CoV-2; coronavirus disease 2019; long COVID; pulmonary embolism; venous thromboembolism; anticoagulant therapy